The 4th European Conference “Europa Postmediaevalis 2024: Patterns and Inspirations”, Warsaw, Institute of Archaeology and Ethnology Polish Academy of Sciences, Faculty of Archaeology Warsaw University, 23-25.04.2024 - Magdalena Bis; Michał Starski; Maciej Trzeciecki (Archaeologia Polona)
An report on this year's "Europa Postmediaevalis 2024: Patterns & Inspirations" conference on post-medieval and modern ceramics, held in Warsaw in April 2024. The conference was the fourth in a series of meetings organised in various European countries in the last six years under the common title Europa Postmediaevalis (2018 in Prague, 2020 – cancelled due to the COVID-19 pandemic, 2022 in Coimbra), on the initiative of the international association ‘Europa Postmediaevalis Research Group’ (see: https://www.europapostmed.eu/en/).